EKSEKUSI HAK TANGGUNGAN SEBAGAI JAMINAN KREDIT DALAM RANGKA PERLINDUNGAN HUKUM BAGI KREDITUR - Kattya Nusantari Putri (Paulus Law Journal, 2020)
Credit Agreement between the creditor and the debtor that is carried out with a guarantee of mortgage sometimes creates problems when there is a default, where the creditor has difficulty executing the object of the Mortgage.This study aims to determine the mortgage execution mechanism as a form of legal protection for creditors and obstacles in carrying out the execution of Mortgage Rights. This study use a normative method with a statutory regulatory approach. The results show that the execution of Mortgage Rights can be carried out in three ways, namely underhand sales, selling through public tenders, and execution by the District Court. The obstacles faced can be in the form of juridical obstacles and non-juridical obstacles.